Konsumsi Oksigen Ikan Uceng Nemacheilus fasciatus (Valenciennes, 1846) pada Kondisi Padat Tebar yang Berbeda - Iswantari, Aliati; Kurniawan, Kurniawan; Priadi, Bambang; Prakoso, Vitas Atmadi; Kristanto, Anang Hari (Indonesian Institute of Sciences, 2019)
Oxygen Consumption of Barred Loach Nemacheilus fasciatus (Valenciennes, 1846) under Different Stocking Densities. In aquaculture system, fish growth is affected by stocking densities. One way to predict the effect of stocking density on growth is to determine fish metabolic rate through oxygen consumption measurements. In Barred loach Nemacheilus fasciatus (Valenciennes, 1846), the information was scarce on oxygen consumption. This study was to analyze the effect of stocking density on oxygen consumption in Barred loach conducted at Research Institute for Freshwater Aquaculture and Fisheries Extension, Bogor in May 2018. Barred loach (total length: 5.79 ± 0.47 cm, weight: 1.32 ± 0.34 g) was observed its oxygen consumption on three different stocking densities (5, 10, and 15 fish/L) by using closed respirometers (volume: 1.4 L) with three replications of each treatment. Measurement of oxygen consumption was carried out under normoxia and hypoxia conditions. In addition, fish behavior and ventilation rate were also observed and recorded according to treatment. The results showed that the highest oxygen consumption of barred loach was found in the stocking density of 5 fish/L (1250.6 ± 128.4 mg O2/kg/h) which was significantly different from the stocking density of 10 fish/L (626.9 ± 46.7 mg O2/kg/h) and 15 fish/L (596.9 ± 48.9 mg O2/kg/h). Meanwhile, oxygen consumption of barred loach under hypoxic conditions decreased significantly compared to normoxic conditions, which was marked by a decrease in their swimming activities. Although the ventilation rate in hypoxic conditions has decreased, the value was not significantly different from those of normoxia condition. Results of this study provide information that an increase in stocking density and hypoxic conditions in barred loach caused a decrease in oxygen consumption rates. In addition, this study showed that the critical oxygen level for barred loach was around 3.1 mg/L